2012
DOI: 10.1021/ja310236m
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Aliphatic Tertiary Amine Chromophore: Fluorescence, Polymer Structure, and Application in Cell Imaging

Abstract: Although photoluminescence of tertiary aliphatic amines has been extensively studied, the usage of this fundamental chromophore as a fluorescent probe for various applications has unfortunately not been realized because their uncommon fluorescence is easily quenched, and strong fluorescence has been observed only in vapor phase. The objective of this study is how to retain the strong fluorescence of tertiary amines in polymers. Tertiary amines as branching units of the hyperbranched poly(amine-ester) (HypET) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
185
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(194 citation statements)
references
References 27 publications
(41 reference statements)
7
185
0
Order By: Relevance
“…Thus, the fluorescence mechanism of conventional conjugated organic dyes is not applicable here, and DPR likely represents a distinct PL mechanism 18 . We hypothesized that the aliphatic tertiary nitrogen is the source of fluorescence, as previously suggested for PAMAM dendrimers 19, 20 . In an early study, monovalent tertiary amines in gas phase showed emissions limited to the range of 250 nm to 400 nm 21, 22 .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, the fluorescence mechanism of conventional conjugated organic dyes is not applicable here, and DPR likely represents a distinct PL mechanism 18 . We hypothesized that the aliphatic tertiary nitrogen is the source of fluorescence, as previously suggested for PAMAM dendrimers 19, 20 . In an early study, monovalent tertiary amines in gas phase showed emissions limited to the range of 250 nm to 400 nm 21, 22 .…”
Section: Resultsmentioning
confidence: 81%
“…In an early study, monovalent tertiary amines in gas phase showed emissions limited to the range of 250 nm to 400 nm 21, 22 . Interestingly, DPRs, PAMAM dendrimers 19, 20, 23 , and amine-containing carbon dots 6, 24 all exhibit maximum excitation at 350 nm–380 nm, and maximum emission at 420–450 nm with significantly stronger intensity in the liquid phase. This dichotomy poses an interesting question of how the mechanism of red shift and increased fluorescence of DPRs in the liquid phase differs from that of monovalent tertiary amines in the gas phase 21, 22, 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Polymer carbon dots (PCDs), a new type of fluorescent carbon dots (CDs), prepared through polymerization and crosslinking between small molecules, have emerged and attracted increasing interest due to their unique structures and excellent properties including low toxicity, excitation‐dependent luminescence, low cost, chemical inertness, and excellent biocompatibility 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. The “core–shell” structure of PCDs distinguishes them from other small molecules and carbon based fluorophores by small molecule/polymer crosslinking into the emission center and holding outer polymer chains synchronously 3, 4, 6. Instead of containing typical conjugated chromophore, whose band gap information is affected by heteroatom doping and finite size effects,20, 21 the PCDs only possess sub‐fluorophores, a potential fluorophore (which are nonconjugated groups such as heteroatom‐containing double bonds like C=N, C=O, N=O and single bonds like amino based groups, C—O), with intrinsically very weak photoluminescence (PL).…”
mentioning
confidence: 99%
“…9 shows that the blue emission of an oxygen-doped tertiary amine (triethylamine) was a key contributor to the uorescence of the poly(amido amine) dendrimer. 20 These ndings all show that tertiary amine or tertiary ammonium groups have taken part in uorescence emission. 13 shows that the distances of the tertiary amines affect the uorescence emission of PAMAM.…”
Section: Theory Calculationsmentioning
confidence: 88%